Clinical Frailty Scale predicts overall survival after colon cancer surgery in people aged 80 years and older: A prospective multicentre observational study - Niemeläinen, Susanna; Hyöty, Marja; Ehrlich, Anu; Jämsen, Esa; Koskensalo, Selja; Kössi, Jyrki; Pinta, Tarja; Vihervaara, Hanna; Huhtala, Heini (Wiley, 2026)
Aim
An increasing number of elective colon cancer surgeries are performed on older patients. Frail patients are at a higher risk of postoperative adverse events and early mortality. This prospective, multicentre, observational study aimed to analyse preoperative screening tools and the long-term survival of older patients having elective colon cancer surgery. The focus was on patients who survived more than 3 months postoperatively, excluding the effect of early postoperative mortality.
Methods
Patients aged ≥80 years with electively operated stage I-III colon cancer were recruited. Prospectively collected data included comorbidities, functional and frailty status, postoperative outcomesand long-term survival. Univariate and multivariable Cox regression analyses were conducted to determine factors associated with long-term survival.
Results
A total of 227 surgical patients were included. Survival rates at 1 and 3 years were 94% and 74% for all patients and 86% and 57% for patients with Clinical Frailty Scale (CFS) 5–9, respectively. In multivariable regression analysis, CFS 5–9 (HR 3.16, 95% CI 1.31–7.63, p = 0.011) and tumour stage III (HR 2.50, 1.16–5.39, p = 0.020) were the patient-related variables affecting survival among those surviving over 3 months postoperatively.
Conclusions
Preoperative frailty assessed by CFS predicts long-term survival in older patients after curative colon cancer surgery.